Medical instruments and devices : principles and practices - Schreiner, Steven (CRC Press, 2015)
Medical Instruments and Devices: Principles and Practices originates from the medical instruments and devices section of The Biomedical Engineering Handbook, Fourth Edition. Top experts in the field provide material that spans this wide field. The text examines how biopotential amplifiers help regulate the quality and content of measured signals. It includes instruments and devices that span a range of physiological systems and the physiological scale: molecular, cellular, organ, and system. The book chronicles the evolution of pacemakers and their system operation and discusses oscillometry, cardiac output measurement, and the direct and indirect methods of measuring cardiac output. The authors also expound on the mechanics and safety of defibrillators and cover implantable stimulators, respiration, and the structure and function of mechanical ventilators. In addition, this text covers in depth: Anesthesia Delivery Electrosurgical Units and Devices Biomedical Lasers Measuring Cellular Traction Forces Blood Glucose Monitoring Atomic Force Microscopy Parenteral Infusion Devices Clinical Laboratory: Separation and Spectral Methods Clinical Laboratory: Nonspectral Methods and Automation Noninvasive Optical Monitoring An offshoot from the definitive "bible" of biomedical engineering, Medical Instruments and Devices: Principles and Practices offers you state-of-the-art information on biomedical instruments and devices. This text serves practicing professionals working in the areas of medical devices and instrumentation as well as graduate students studying bioengineering, instrumentation, and medical devices, and it provides readers with a practical foundation and a wealth of resources from well-known experts in the field